Stability of corn cultivars in three ecosystems of Brazilian Northeast - Carvalho, Hélio Wilson Lemos de; Leal, Maria de Lourdes da Silva; Santos, Manoel Xavier dos; Monteiro, Antônio Augusto Teixeira; Cardoso, Milton José; Carvalho, Benedito Carlos Lemos de (Pesquisa Agropecuaria Brasileira, 2000)
The production stability of twelve corn genotypes was evaluated in 75 different environments of the Coastal Tablelands, "Agreste" and "Sertão" ecosystems, during the 1995, 1996 and 1997 growing seasons in randomized block design with three replications, aiming at the recommendation of adapted materials. High mean productivities were slightly similar at ecosystem level. Coastal Tablelands should be highlighted as a new competitive area of corn production. Hybrids showed better environment adaptation than cultivars, BR 3123 showing the best yielding in all the three ecosystems in spite of being the most exigent under unfavourable conditions. Except for BR 2121, all hybrids had good production stability in all of the environments considered (R2 > 80%). Among the cultivars with better adaptation, only BR 106 showed low stability in these environments (R2 = 75%). For the Brazilian Northeast, BR 5033 cultivar was the ideal genotype proposed by this model.